(untitled) (Mustansiria Dental Journal, 2018)
The temporomandibular joint (TMJ) may be affected by inflammatory, traumatic, infectious, congenital, and developmental, as seen in other joints. However, the most common affliction of the TMJ and masticatory apparatus is a group of functional disorders with associated pain that occurs predominantly in women and was previously known as the TMJ pain dysfunction syndrome. Since 1978, there have been substantial changes in the study of etiologic factors, pathophysiology, diagnosis, and management of what are now called temporomandibular disorders (TMD).(1)The general perception that all symptoms in the head, face, and jaw region without an identifiable cause constitute a "TMJ" problem is clearly unfounded. Although some oral lesions, such as torus palatinus and torus mandibularis are normal variants, but require prompt diagnosis and sometime treatment to reduce the potential for serious complication and enhance prosthodontic treatment. The purpose of this study is to inspect the relation of TMJ dysfunction syndrome to the presence of oral exostosis, and find the prevalence of torus palatinus (TP) and torus mandibularis (TM) The sample consisted of 932 teachers, 301 males and 631 females were examined for the presence of TMD, TP and / or TM. Analysis was carried out according to age, gender, TMJ dysfunction and the presence of TP and TM. Results indicated that 123(16.1%) had at least one symptoms of TMD, where as 49 (5.3%) had TP; and 67 (7.2) had TM. The male: female prevalence ratios of TP and TM were 1: 3.42 and 1: 1.81 respectively. The results revealed that significant relationship between TMD and tori, and increase in percentage of mandibular tori with the presence of TMJ dysfunctional syndrome more than maxillary tori were found. TP and TM were more frequent in females and there is significant relation between the TP and TM with presence of TMJ dysfunction syndrome ( P< 0.05 ) especially TM , the presence of TM might be useful to look for sign of dysfunction.